Internet of things (IoT) based I-V curve tracer for photovoltaic monitoring systems - H. B. Chi; M. F. N. Tajuddin; N. H. Ghazali; A. Azmi; M. U. Maaz (Institute of Advanced Engineering and Science, 2019)
This paper presents a low-cost PV current-voltage or I-V curve tracer that has the Internet of Things (IoT) capability. Single ended primary inductance converter (SEPIC) is used to develop the I-V tracer, which is able to cope with rapidly changing irradiation conditions. The I-V tracer control software also has the ability to automatically adapt to the varying irradiation conditions. The performance of the I-V curve tracer is evaluated and verified using simulation and experimental tests.